Spremljanje vključenosti ciljev trajnostnega razvoja v pedagoški, znanstvenoraziskovalni in upravljalski vidik delovanja visokošolskega zavoda - Arbeiter, Jana (Teorija in praksa, 2024)
The article presents a methodological approach to mapping and evaluating the inclusion of Sustainable Development Goals (SDGs) in the pedagogical, research and managerial activities of the Faculty of Social Sciences at the University of Ljubljana, Slovenia. Through keyword mapping related to the SDGs, the mentioned approach assesses the presence of sustainability-related content in course curricula, research publications, and managerial operations at the Faculty. The methodology enables a systematic review of sustainability-oriented content and helps with aligning the Faculty’s activities with sustainable development practices. The research points key areas of strength and the need for further integration of the SDGs in academic and administrative domains.
Keywords: cilji trajnostnega razvoja; education; izobraževanje; mapiranje; mapping; sustainable development; sustainable development goals; Trajnostni razvoj; universities; univerza; Univerza v Ljubljani, Fakulteta za družbene vede